Modern concepts and practices in cardiothoracic critical care - Evans, Adam S.; Kerr, Gregory E.; Chiung, Insung; Varghese, Robin; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This book brings together the most recent research and current issues facing medical professionals and patients in intensive cardiovascular care to provide the necessary tools and resources for improved health and medical care and includes chapters on safety, ethics, and specific surgical techniques for all those who care for patients following cardiothoracic surgery"--Provided by publisher.
Introduction to care of the cardiac surgical patient -- Preoperative assessment and optimization -- Pharmacology in the cardiothoracic ICU -- A Systematic approach to cardiothoracic critical care -- Surgical techniques and postoperative concerns -- Monitoring the postoperative cardiac patient.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 09/12/2015).
Keywords: Cardiac intensive care; Cardiovascular Diseases -- surgery; Thoracic Diseases -- surgery; Critical Care -- methods; Acute coronary syndromes; Cardiovascular system; Coronary artery disease; Patient monitoring; Pharmacology; Postoperative concerns; Surgical techniques; Electronic books